2011
DOI: 10.1016/j.rmed.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Validation and agreement across four versions of the asthma control questionnaire in patients with persistent asthma

Abstract: All ACQ versions have similar and strong psychometric properties. Classifications of change over time using the original ACQ and a six-item version without SABA use provided generally fair to moderate agreement with the international guidelines criteria for asthma control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 18 publications
(21 reference statements)
1
28
0
Order By: Relevance
“…13,14,19 The correlations between the ACQ and the shortened versions were high (r ϭ 0.87 with ACQ-5, 0.98 with ACQ6a, and 0.92 with ACQ-6b). 57 A post hoc analysis of 2 large clinical trials showed that all versions of the ACQ were strongly correlated with each other and with the overall score from the AQLQ for both baseline and change scores. 57 In another study, Juniper et al 58 reported that these 3 shortened versions can be used in large clinical trials without loss of validity or change in interpretation.…”
Section: Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…13,14,19 The correlations between the ACQ and the shortened versions were high (r ϭ 0.87 with ACQ-5, 0.98 with ACQ6a, and 0.92 with ACQ-6b). 57 A post hoc analysis of 2 large clinical trials showed that all versions of the ACQ were strongly correlated with each other and with the overall score from the AQLQ for both baseline and change scores. 57 In another study, Juniper et al 58 reported that these 3 shortened versions can be used in large clinical trials without loss of validity or change in interpretation.…”
Section: Validitymentioning
confidence: 99%
“…57 A post hoc analysis of 2 large clinical trials showed that all versions of the ACQ were strongly correlated with each other and with the overall score from the AQLQ for both baseline and change scores. 57 In another study, Juniper et al 58 reported that these 3 shortened versions can be used in large clinical trials without loss of validity or change in interpretation. Also, when the 4 versions were compared with each other, substantial concordances in both cross-sectional and longitudinal va-lidity were noted.…”
Section: Validitymentioning
confidence: 99%
“…The overall score is the average of the individual item scores, ranging from 0 (totally controlled) to 6 (severely uncontrolled). Abbreviated versions of the ACQ are also available: the ACQ-5, which scores symptoms only, that is, omits bronchodilator use and FEV 1 , and the ACQ-6, which scores symptoms and bronchodilator use (25,26).…”
Section: Overview Of the Acqmentioning
confidence: 99%
“…For determining the control level, 2 threshold values were described. The mark ≤0,75 points means that BA is controlled, and the value ≥1,5 -uncontrolled [11]. The interval from 0,75 to 1,5 -so-called "grey zone", from our point of view, it may be assessed as a partial control of asthma.…”
Section: Introductionmentioning
confidence: 99%
“…The data of independent studies give proofs about validity of the questionnaire for BA control, and the possibility of its use in the general practice and for clinical studies [11,12]. The questionnaire includes questions about BA symptoms, use of bronchodilators with a short-term action (ACQ-6), and also the volume of a forced exhalation for 1 second (FEV1) (ACQ-7) [13].…”
Section: Introductionmentioning
confidence: 99%